Cardiorespiratory responses reach vigorous‐intensity levels during simulated gameplay of arena polo. Issue 3 (7th January 2020) - Pritchard, Abby; Barthel, Samuel; Ferguson, David
Abstract: Arena polo is surging in popularity, but limited information exists on the physiological demands of polo. The goal of this study was to document the oxygen consumption (VO2 ), ventilation (VE), and respiratory exchange ratio (RER) in conjunction with heart rate (HR) involved in arena polo to better inform players of the physical requirements of participation. Cardiorespiratory responses were measured using a portable telemetric oxygen analyzer coupled with a heart rate monitor on five female arena polo players. Peak aerobic capacity of each player was determined on a treadmill in a laboratory setting. Data were recorded on each player during designated sessions which included a prescribed and free‐choice warm‐up, mock gameplay (Chukker), and five‐minute recovery. Descriptive statistics for each variable (Mean ± SE) were calculated for each period. A one‐way ANOVA with repeated measures was performed to determine differences among periods. Chukker produced the highest cardiorespiratory responses out of all the periods ( P < .001) with 89 ± 1% HRpeak and 62 ± 2% VO2peak, except for RER which was highest during recovery (0.88 ± 0.01, P < .001). As evidenced by this study, arena polo constitutes intense exercise comparable to traditional sports above warm‐up and recovery.